EFEKTIVITAS PELAYANAN JAMKESDA PADA PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH H HASAN BASRY KANDANGAN - Yusran Fahmi (Jurnal PubBis, 2019)
The purpose of this study was to determine the extent to which the effectiveness of Jamkesda services and identify the inhibiting factors that affect the effectiveness. Jamkesda Technical Service Unit can be categorized effectively if the community gets the ease of service, obtains low cost, fast, appropriate and satisfying service. The researcher used a phenomenological approach, with the technique of collecting questionnaire data, observation and interviews, in the Jamkesda service outpatient treatment with 150 respondents. The effectiveness of the service is measured through the Community Satisfaction Index by referring to the Decree of the Minister of Administrative Reform Number 25 of 2004. The results of the study include: the level of suitability of services with standard operating procedures, and the level of implementation of service programs can be said to be effective (average value of 3.28 categories of perception is very good, the average conversion value is 81.86, the conversion interval value is also very good). The inhibiting factor is not too influential because the value of the average element is 3.28 the category of perception is still very good. High service effectiveness is generated by the high level of compliance and knowledge of service personnel on the implementation of Standard Operating Procedures so that programs and activities are carried out properly. Factors that affect the field indirectly support the achievement of high effectiveness. It is recommended to continue to support programs and activities through the allocation of sufficient funds for the ability of officers to provide services, speed of service, and complete infrastructure facilities for the Jamkesda Technical Implementation Unit. Keywords: service effectiveness; service performance